1,N6-ethenoadenine and other Fluorescent Nucleobase Analogs as Substrates for Purine-Nucleoside Phosphorylases: Spectroscopic and Kinetic Studies - Wierzchowski, Jacek; Stachelska-Wierzchowska, Alicja; Wielgus-Kutrowska, Beata; Bzowska, Agnieszka (Current Pharmaceutical Design, 2017)
Background: Purine-nucleoside phosphorylase (PNP) is known as a tool for the synthesis of various nucleosides and nucleoside analogues. Mechanism, properties, molecular diversity and inhibitors of PNP, particularly these of pharmacological significance, are briefly characterized. Methods: UV and fluorescence spectroscopy was used for kinetic experiments, and HPLC chromatography for product analyses. Results: Applications of various forms of PNP to synthesis of selected fluorescent nucleosides, particularly ribosides of 1,N6-ethenoadenine and various 8-azapurines (triazolo[4,5-d]pyrimidines) are reviewed. Different specificity of various PNP forms is described towards nucleobase and analog substrates as well as variable ribosylation sites observed in some reactions, with a possibility to further modify these features via the site-directed mutagenesis. Conclusion: Present and future applications of the fluorescent or fluorogenic ribosides are discussed, with particular emphasis on biochemical and clinical analyses with improved sensitivity.
Keywords: nucleoside analogs